Whole-Mars Decompression Dynamics - Herndon, J. Marvin (European Journal of Applied Sciences, 2022)
Whole-Mars Decompression Dynamics is a new planetary science paradigm that follows from observations that Mars, like Earth, primarily formed by condensing and raining out from within a giant gaseous protoplanet, whose massive shell of gases and ices compressed the rocky planet, but was subsequently stripped away by the super-intense T-Tauri phase solar winds associated with thermonuclear ignition of the sun. For a brief period, perhaps one billion years, Mars’ nuclear fission planetocentric reactor produced the planet’s magnetic field and supplied the lost heat of protoplanetary compression which enabled whole-Mars decompression to proceed. Through the process of mantle decompression thermal tsunami, the stored energy of protoplanetary compression also heated the crust and provided a thermal barrier to the downward percolation of water. Presumably contemporaneous with demise of the magnetic field, the whole-Mars decompression process subsided, concomitantly transforming Mars from warm and wet to cold and dry. Whole-Mars Decompression Dynamics provides different possible interpretations of Martian features and events, including the perimeter-features of Valles Marineris being circum-perimeter tears like Norwegian fjords, surface pits being the consequence of hydrogen geysers like on Mercury, and implications where one might hope to find Martian hydrocarbon deposits.